Nature-based therapeutics: A collaborative research agenda promoting equitable access and environmental stewardship. Issue 1 (February 2022) - Alexander, Gina K.; Brooks, Vicki
ABSTRACT: Background: Given the duration and intensity of the COVID-19 pandemic, with strict emphasis on social distancing, many individuals and families are experiencing social isolation. The need to explore effective strategies for health promotion and wellness is clear. Aim: The purpose of this report is to highlight evidence supporting the health benefits of nature-based therapeutics and to describe the exploratory and translational research agenda for a nurse-led program entitled RxPLORE TM : Prescribing Life Outdoors and Real Exploration. Methods: Integrative review of the current state of evidence for nature-based therapeutics and operationalisation of a nature-based health promotion framework as the foundation of a PhD-DNP collaborative program of research. Discussion: Amidst the unfolding crisis of the COVID-19 pandemic, the value of nature-based therapeutics is becoming more widely recognised, as are layers of disparities in access to nature. A nurse-led team proposes a program of research outlining priorities for the translation of current evidence into practice and for the investigation of gaps in the evidence base that will inform future recommendations for nature-based health promotion. The initial population of focus is children and families. Conclusion: Prescribing nature is a strategy to promote health and wellness throughout the lifespan. For all populations to experience the health-promoting benefits of nature, nurses engage community members and collaborate across sectors to advocate for equitable access to nature and environmental stewardship through conservation practices.